Faktor-faktor yang Mempengaruhi Tingkat Pendapatan Usaha Laundry di Kecamatan Banjarmasin Barat Kota Banjarmasin - Maulidia, Arida; Fahrati, Eny (PPJP Universitas Lambung Mangkurat, 2023)
This study (1) aims to determine the effect of capital, price, and quantity of laundry on laundry business income in West Banjarmasin District, Banjarmasin City. (2) To determine the most dominant factor influencing laundry business income in West Banjarmasin District, Banjarmasin City. This study used 20 respondents who were laundry business owners in the West Banjarmsain District, Banjarmasin City. The data in this study were then processed using multiple linear regression analysis using Eviews 10 software. The results of this study indicate that together, the factors of capital, price, and quantity of laundry affect the income of the laundry business in the West Banjarmasin District, Banjarmasin City. The most dominant factor in influencing the income of the laundry business in West Banjarmasin District, Banjarmasin City, is the washing quantity factor.